Analysis of reticulin fiber pattern in lymph nodes with metastasis from oral squamous cell carcinoma - Shanmukha Raviteja Yinti; Srikant Natarajan; Karen Boaz; Amitha J Lewis; Jay Pandya; Supriya Nikita Kapila (Wolters Kluwer Medknow Publications, 2015)
Introduction: The aim of the study was to determine the susceptibility of lymph nodes to metastasis in oral squamous cell carcinoma (OSCC) by analyzing the alterations in reticulin fiber pattern. Materials and Methods: This retrospective study on 30 cases of OSCC had 15 cases that presented with lymph node metastasis (test group) and 15 cases without metastatic episodes (control group). Four micron thick sections of the tumor proper and the resected lymph nodes of the cases were stained with hematoxylin and eosin, and Gordon and Sweet's stain for reticulin. Statistical analysis of the variations in the staining patterns of reticulin at the invasive tumor front (ITF), involved and uninvolved lymph nodes were done with Statistical Package for Social Sciences (SPSS) 15 version using chi-square test. Results: The assessment of reticulin fiber patterns at the ITF, cortical and medullary areas of lymph nodes in test cases showed thin, long individual fibers, as compared to thick, shorter interlacing fibers that were seen in control cases. The peritumoral and uninvolved areas in metastatic lymph nodes of almost all test cases showed very scant fibers. Conclusion: Reticulin pattern alteration by aggressive tumors may be appreciated as a part of the wide spectrum of "proneoplastic" stromal alterations. The histopathologist can discern these changes and thereby aid the clinician in predicting tumor behavior, the clinical course of the disease, and weighing the prognostic implications.